2021
DOI: 10.3390/ma14112846
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Technology for Palm Oil Mill Effluent (POME) Wastewater Treatment: Current Progress and Future Perspective

Abstract: The palm oil industry produces liquid waste called POME (palm oil mill effluent). POME is stated as one of the wastes that are difficult to handle because of its large production and ineffective treatment. It will disturb the ecosystem with a high organic matter content if the waste is disposed directly into the environment. The authorities have established policies and regulations in the POME waste quality standard before being discharged into the environment. However, at this time, there are still many facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 184 publications
(251 reference statements)
0
20
0
Order By: Relevance
“…3,[5][6][7] Furthermore, POME can be difficult in handling, as the production of POME often comes in a massive form and the conventional POME treating method is ineffective where long duration will be needed for POME degradation. 8,9 In Malaysia, POME has been treated conventionally with biological treating system, which is also known as the open ponding treatment. 10 Although having such POME treating system, POME has still been identified as one of the major industrial pollutants in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[5][6][7] Furthermore, POME can be difficult in handling, as the production of POME often comes in a massive form and the conventional POME treating method is ineffective where long duration will be needed for POME degradation. 8,9 In Malaysia, POME has been treated conventionally with biological treating system, which is also known as the open ponding treatment. 10 Although having such POME treating system, POME has still been identified as one of the major industrial pollutants in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…3,5–7 Furthermore, POME can be difficult to handle, as the production of POME often occurs on a massive scale and the conventional POME treatment method is ineffective where a long duration is needed for POME degradation. 8,9…”
Section: Introductionmentioning
confidence: 99%
“… 17–19 Among these approaches, photocatalysis has already been employed in several applications for years with commendable success, such as water treatment, pollutant degradation, bio-organic waste treatment, and bactericidal drugs. 20–22 This diverse range of applications has stimulated great research interest, and as a result, photocatalysis has recently emerged as a promising solution for sustainable environmental nitrogen fixation. In 1977, Guth et al reported on the nitrogen reduction reaction over a TiO 2 photocatalyst and Fe 2 O 3 as a cocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used POME waste treatment is conventional treatment using an open pond system through anaerobic and aerobic decomposition processes. The disadvantage of this system is that apart from requiring a large area of land and a long retention time, it can also emit harmful gases such as methane gas and cause sludge build-up [ 3 ]. Therefore, conventional treatment is very inefficient for treating POME.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, conventional treatment is very inefficient for treating POME. In recent years, various treatment methods have been developed to eliminate and reduce POME pollution [ 3 ]. These methods include composting [ 4 ], fermentation [ 5 ], coagulation flocculation [ 6 ], adsorption [ 7 ], flotation, membrane technology [ 8 ], steam reforming [ 9 ], and advanced oxidation processes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%